Field Size-based Packet Header Anomaly Detection with Rule-Based Normal Profile Updating for Intrusion Detection - S, Vishnu Prasad; B, Malarkodi; KG, Michael Kutty (2024 IEEE International Conference on Signal Processing, Informatics, Communication and Energy Systems (SPICES), 2024)
Packet Header Anomaly Detection, or PHAD, is a technique for detecting network intrusion. It assigns scores to a packet using some method and uses these scores to predict whether this packet is benign or anomalous. In this method, the genuine packets usually seen in a network are used to create the profile of header fields. During testing, packet header fields are extracted and compared with the values in this profile. A score is assigned to each packet based on the presence or absence of each header field of the packet in the profile. This score is compared with a threshold, and a label is assigned to the packet. Researchers employ two methods for generating the score: stationary and non-stationary methods. The main issue with this PHAD technique is the large amount of false alarms generated. To reduce these false alarms without compromising other parameters, a modified PHAD scheme with a new scoring method and the introduction of a mechanism to update the profile during the testing phase is proposed in this work. The proposed method was tested on two publicly available datasets, and the results show that the technique can reduce false alarms by about 11% without causing any reduction in the other parameters.